(untitled) (Experimental biology, 2018)
In recent years, increasing attention is paid to the ecological and global issues related to environmental pollution by heavy metals and persistent organic pollutants. Pollution by metals is very noticeable in mining areas, as well as around foundries and metallurgical plants. Persistent organic pollutants are found everywhere, which can be explained by long-distance transport by wind and water, they remain for a long period of time in the environment, have the capacity for cumulation and can pass from one species to another through the food chain. The problems associated with the presence of heavy metals and POPs in the environment is relevant for the country. In this regard, the purpose of this work was to determine the points of contamination with contaminants for further studies the effect of these compounds on the food chain. This article aimed to summarize data reporting concentrations of environmental contaminants in various regions of Kazakhstan. In the course of the work, was made an analysis of scientific articles measured concentrations of contaminants in Kazakhstan, primarily in environmental matrices (soil, water, plants) and in livestock products.Thus, territories containing elevated concentrations of heavy metals, organic pollutants and pesticides in various environmental components were identified. The obtained data have an important theoretical value and contain useful information for further research. Key words: environmental pollution,heavy metals, organic pollutants, pesticides.